2001
DOI: 10.1159/000063223
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Adhesiveness: Effects of the SH Metabolite of Erdosteine (Mucoactive Drug) plus Clarithromycin versus Clarithromycin Alone

Abstract: After metabolization, erdosteine (a mucoactive drug) produces an active metabolite (Met I) with an SH group that is capable of opening disulphide bonds, including those of pilin, a protein of bacterial fimbriae. This induces stereochemical conformational changes that interfere with the binding of bacterial adhesins (fimbriae) to receptors on eukaryotic cells. At subinhibitory concentrations, the macrolide clarithromycin inhibits the expression of adhesins on bacterial cell surfaces. The addition of 5 and 10 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 12 publications
1
8
1
5
Order By: Relevance
“…It also agrees with that of Ndour et al [23] who suggested that the decrease of attachment of H. influenzae with epithelial cells after treatment with carbocysteine was possibly due to the decrease of the mammalian cell surface charge. Conversely, the results of the present study is inconsistent with that of Braga et al [22] who found that the mucoactive drug erdosteine interferes with bacterial adherence via inducing stereochemical conformational changes in the structure of pilin, a protein of bacterial fimbriae. It is noteworthy that the antiadherent effect of some mucolytics observed in this study was significantly higher upon using M1 (only mammalian cells come in contact with the drug) as compared to M3 test model (both bacteria and mammalian cells come in contact with the drug simultaneously; P≤0.05).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It also agrees with that of Ndour et al [23] who suggested that the decrease of attachment of H. influenzae with epithelial cells after treatment with carbocysteine was possibly due to the decrease of the mammalian cell surface charge. Conversely, the results of the present study is inconsistent with that of Braga et al [22] who found that the mucoactive drug erdosteine interferes with bacterial adherence via inducing stereochemical conformational changes in the structure of pilin, a protein of bacterial fimbriae. It is noteworthy that the antiadherent effect of some mucolytics observed in this study was significantly higher upon using M1 (only mammalian cells come in contact with the drug) as compared to M3 test model (both bacteria and mammalian cells come in contact with the drug simultaneously; P≤0.05).…”
Section: Discussioncontrasting
confidence: 99%
“…The observed antiadherent effect of these mucolytics comes in accordance with that of Riise et al [10] who reported that the mucolytic N-acetyl cysteine reduced the adherence of S. pneumoniae and H. influenzae to oropharyngeal epithelial cells. Similar observation was reported by Braga et al [22] regarding the adherence of S. aureus to human mucosal cells. Moreover, it agrees with that reported by Zheng et al [11] who proposed that one of the mechanisms of mucoregulating drugs to decrease the episode of respiratory infections is by inhibiting the attachment of bacteria to the upper respiratory tract.…”
Section: Discussionsupporting
confidence: 90%
“…NAC is known to disrupt disulphide bonds, therefore this protein might be a target for NAC which would impair its folding and, consequently, flagellar assembly. Similarly erdosteine, a mucolytic agent, is capable of opening disulphide bonds of pilin, a constituent of the bacterial motility mechanism in Staphylococcus aureus (Braga et al, 2001).…”
Section: Figurementioning
confidence: 99%
“…Erdosteine is a more recently developed mucoactive drug which addresses some of the problems associated with older drugs in this class [ 13 ]. Erdosteine has antioxidant and anti-inflammatory properties, but also modulates bacterial adhesiveness, properties potentially of value in the treatment or prevention of exacerbations [ 14 16 ]. Preliminary clinical data (EQUALIFE study) suggested that erdosteine, as an add-on therapy, could reduce the exacerbation rate and time spent in hospital, and improve health-related QoL in COPD patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%